Wage inequality in Germany : disentangling demand and supply effects - Michael Stimmelmayr (Center for Economic Studies and ifo Institute (CESifo), 2009)
In this paper we conduct a counterfactual analysis and estimate the quantitative importance of demand and supply effects on wage inequality in Germany using a dynamic computable general equilibrium (CGE) model of the Auerbach-Kotlikoff (1987) type. Specifically, the methodological contribution of our dynamic CGE model refers to the three-level constant elasticity of substitution production function and the endogenous labor supply of three different skill types, which enable us to isolate the impact of capital-skill complementarity (i.e., demand effects) and varying skill-specific labor supply (i.e., supply effects) on the evolution of the skill premia as defined by the 9th to 1st, the 9th to 5th, and the 5th to 1st decile limit of earnings. In short, our simulation results show that the complementarity effect has a particularly strong positive impact on the skill premium of the high-skilled, while the quantity effect counteracts the complementarity effect and exerts an alleviating pressure on the skill premium of the high-skilled. In quantitative terms, the complementarity effect raises the skill premium of the 9th to 1st and the 9th to 5th decile limit of earnings by more than 1.0 and 0.8 percent per year, respectively. By contrast, the quantity effect reduces both above-mentioned skill premia by almost 0.3 and 0.45 percent per year, respectively. Even though the complementarity and the quantity effects work in opposite directions, the complementarity effect has a much stronger impact on the skill premia of the high-skilled compared with the quantity effect.
Keywords: J31; J23; C68; 330; capital-skill complementarity; skill premium; wage inequality; skill-specific labor supply; dynamic general equilibrium analysis; Lohnstruktur; Arbeitsnachfrage; Qualifikation; Arbeitsangebot; CES-Produktionsfunktion; Allgemeines Gleichgewicht; Dynamisches Gleichgewicht; Deutschland